2008
DOI: 10.3174/ajnr.a0806
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcome and Ischemic Complication after Treatment of Anterior Choroidal Artery Aneurysm: Comparison between Surgical Clipping and Endovascular Coiling

Abstract: BACKGROUND AND PURPOSE:Although coiling has been favorably comparable with clipping for treatment of most intracranial aneurysms, there is a controversy on which modality is safer for anterior choroidal artery (AchoA) aneurysm. We retrospectively evaluated the clinical outcomes and treatmentrelated complications after surgical clipping and endovascular coiling of AchoA aneurysms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 11 publications
2
33
0
Order By: Relevance
“…The incidence of permanent AChA syndrome after surgical clipping of an AChA aneurysm has consistently been reported to range from 5.3% to 15.7%1,5,6,10,11,17,20). When compared with surgical series, endovascular series have a much lower incidence of AChA insufficiency, although only a few series have been reported8-10,15,16). However, the favorable surgical outcomes of the current series, no occurrence of permanent AChA syndrome in the 62 patients, would seem to suggest that the risk of AChA insufficiency can be reduced with appropriate surgical techniques and intraoperative monitoring18).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The incidence of permanent AChA syndrome after surgical clipping of an AChA aneurysm has consistently been reported to range from 5.3% to 15.7%1,5,6,10,11,17,20). When compared with surgical series, endovascular series have a much lower incidence of AChA insufficiency, although only a few series have been reported8-10,15,16). However, the favorable surgical outcomes of the current series, no occurrence of permanent AChA syndrome in the 62 patients, would seem to suggest that the risk of AChA insufficiency can be reduced with appropriate surgical techniques and intraoperative monitoring18).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the endovascular coiling of AChA aneurysms, the previous reports show that endovascular treatment is effective for preventing aneurysmal ruptures and recurrent bleeding with low morbidity and mortality rates8-10,15,16). However, there are significant concerns with an endovascular procedure, including thrombotic occlusion of the AChA, a fatal procedural aneurysm rupture, and high recurrence rate of occluded aneurysms over a long-term period8-10,14-16).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding monitoring AChA patency during aneurysm treatment, endovascular treatment may have an advantage as a result of continued monitoring of vessel patency angiographically throughout the procedure. 13 There were 8 aneurysms treated with endosaccular coiling in our study, none of which resulted in ischemic outcomes. These patients were carefully selected for endosaccular coiling owing to their poor presenting Hunt and Hess grade and favorable vascular anatomy.…”
Section: Endovascular Treatmentmentioning
confidence: 72%
“…8 Kim et al 13 suggested that the overall outcome as determined by a modified Rankin Scale score is roughly equivalent (83.8% coil and 88.6% clip). Regarding monitoring AChA patency during aneurysm treatment, endovascular treatment may have an advantage as a result of continued monitoring of vessel patency angiographically throughout the procedure.…”
Section: Endovascular Treatmentmentioning
confidence: 99%